The impact of the day of the week on the financial market: an empirical investigation on cryptocurrencies - Arzova, Sabri Burak; Koy, Ayben; Sahin, Bertac Sakir (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThis study investigates the effect of the day of the week on the volatility of cryptocurrencies. Thus, we reveal investors' perceptions of the day of the week.Design/methodology/approachThe EGARCH model consists of the day of the week for 2019-2022 and the volatility of 11 cryptocurrencies.FindingsEmpirical results show that the weekend harms cryptocurrency volatility. Also, there was positive cryptocurrency volatility at the beginning of the week. Our findings show that weekdays and weekends significantly impact cryptocurrency volatility. Besides, cryptocurrency investors are sensitive to market movements, disclosures, and regulations during the week. Holiday mode and cognitive shortcuts may cause cryptocurrency traders to remain passive on weekends.Research limitations/implicationsThis study has some limitations. We include 11 cryptocurrencies in the analysis by limiting cryptocurrencies according to market capitalizations. Further studies may analyze a larger sample. In addition, further studies may examine the moderator and mediator effects of other financial instruments.Practical implicationsThe empirical results have research, social and practical conclusions from different aspects. Our analysis may contribute to determining trading strategies, risk management, market efficiency, regulatory oversight, and investment decisions in the cryptocurrency market.Originality/valueThe calendar effect in financial markets has extensive literature. However, cryptocurrencies' weekday and weekend effect needs to be adequately analyzed. Besides, studies analyzing cryptocurrency volatility are limited. We contribute to the literature by investigating the impact of days of the week on cryptocurrency volatility with a large sample and current data.
Keywords: Calendar effect; Weekend effect; Cryptocurrency market; EGARCH; G11; G12; G14; G17; G40; RETURN; INFORMATION; VOLATILITY; LIQUIDITY; SENTIMENT; PRICE; NEWS; Business & Economics